HUBUNGAN GENDER TERHADAP KEMAMPUAN PEMAHAMAN KONSEP PADA MATERI SEL PESERTA DIDIK KELAS XI IPA3 - Indrawati Indrawati (Ensiklopedia Education Review, 2023)
The ability to understand concepts in learning needs to be emphasized because there are still many students who do not understand cell material in biology subjects. Cell material is material that is considered difficult for students, especially regarding cell structure for both female students and male students. The purpose of this study was to determine the relationship between the ability to understand concepts and students' gender regarding cell material. The research was conducted at SMAN I Pasirpenyu in class XI IPA which consisted of 34 students. This study uses a quantitative associative method. The data collection technique in this study was in the form of a written test. The data analysis technique uses three main steps, namely data description, assumption test and conclusion drawing. The results of the descriptive study showed that the average test result for the ability to understand the concept of female students was 78,143 while the average test result for the ability to understand the concept of male students was 72,077. The results of the hypothesis test using the correlation test obtained a value of Sig (2-tailed) <0.05). This shows that H1 is accepted, this means that there is a relationship between the ability to understand concepts and the gender of students.Keywords: Gender; Concept Understanding Ability; Cell.